PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER NATURE EDUCATE WORLD UNTUK ANAK USIA DINI - Farid Al Din Al Barosi, - (2022)
The objectives of this study are (1) to determine the determination of material in the development of learning media Nature Educate World (NEW). (2) To find out the design and development process of Nature Educate World (NEW) as a learning medium. (3) To find out the implementation of Nature Educate World (NEW) learning media in the learning process (4) To find out the user's response to Nature Educate World (NEW) as a learning medium for early childhood. Based on researchers' observations of students, parents and teachers, the lack of media innovation is one of the obstacles in learning. Therefore, researchers are interested in developing a computer-based learning media that uses a combined model of games and also subject matter used for early childhood, namely material about animal recognition. This research is a Design & Development (D&D) study with steps adapted from the model of Ken Peffers, et al. This research was conducted by involving media experts, material experts, and users. The results of this study are in the form of computer-based learning media Nature Educate World (NEW) which contains animal introduction materials. Then the results of the study showed that the developed media was suitable for use in early childhood learning, as seen from the validation results of media experts, namely 80% of the first media experts and 78% of the second media experts. Furthermore, it can be seen from the results of the user questionnaire showing that the average percentage of answers for each aspect is 91%, which means that Nature Educate World (NEW) media can be accepted and used for early childhood learning.